Public sector organisations as agents of transformations: A framework for analysing structural changes within Public Sector Organisations (PSO) - Thomas Jackwerth; Nof Afghani; Stephanie Daimer; Ralf Lindner; Florian Wittmann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2023)
The demand for the public sector to be more involved in transitions towards a more sustainable society has raised questions about what capabilities are needed for Public Sector Organisations (PSOs) to play a part in tackling important societal issues such as climate change. To do this, PSOs need new capabilities at three levels. Firstly, the capability to reflect and assess the complexity of societal issues. Secondly, the capability to collaborate across sectors, as well as with non-state actors, in order to tackle complex problems. Lastly, the capability to gather and analyze different types of data. To assume this active role, PSOs must also cultivate an organisational culture that motivates individuals to engage in addressing these issues. This cultural shift cannot be planned in detail but can be shaped by changes in the formal structures of the PSO. Up to this point, little research has been conducted on the capabilities PSOs require to become change agents. This article offers a model to systematically identify these capabilities so that PSOs can assume an active role in leading transformation processes.
Keywords: 330; Public sector organisations (PSO); Structrural changes